Leukotrienes Are Dispensable for Vaginal Neutrophil Recruitment as Part of the Immunopathological Response During Experimental Vulvovaginal Candidiasis - Yano, Junko; White, David J.; Sampson, Anthony P.; Wormley, Floyd L.; Fidel, Paul L. (Frontiers in Microbiology, 2021)
Recruitment of polymorphonuclear neutrophils (PMNs) into the vaginal lumen is the hallmark of an acute immunopathologic inflammatory response during vulvovaginal candidiasis (VVC) caused by Candida albicans. Recurrent VVC (RVVC) remains a chronic health burden in affected women worldwide despite the use of antifungal therapy. Based on the role Leukotrienes (LTs) play in promoting inflammation, leukotriene-receptor antagonists (LTRAs) targeted for LTB4 (etalocib) or LTC4, LTD4 and LTE4 (zafirlukast or montelukast) have been shown to reduce inflammation of epithelial tissues. An open label pilot study using long-term regimens of zafirlukast in women with RVVC indicated the potential for some relief from recurrent episodes. To investigate this clinical observation further, we evaluated the effects of LT antagonistic agents and LT deficiency on the immunopathogenic response in a mouse model of VVC. Results showed that mice given daily intraperitoneal injections of individual LTRAs, starting 2 days prior to vaginal inoculation with C. albicans and continuing through 14 days post-inoculation, had no measurable reduction in PMN migration. The LTRAs were also ineffective in reducing levels of the hallmark vaginal inflammatory markers (S100A8, IL-1β) and tissue damage (LDH) associated with the immunopathogenic response. Finally, LT-deficient 5-lipoxygenase knockout mice showed comparable levels of vaginal fungal burden and PMN infiltration to wild-type mice following inoculation with a vaginal (ATCC 96113) or laboratory (SC5314) C. albicans isolate. These results indicate that despite some clinical evidence suggestive of off-target efficacy of LTRAs in RVVC, LTs and associated signaling pathways appear to be dispensable in the immunopathogenesis of VVC/RVVC.